Biomechanical pathways of dentoalveolar fibrous joints in health and disease. Issue 1 (18th December 2019) - Lin, Jeremy D.; Ryder, Mark; Kang, Misun; Ho, Sunita P.
Abstract: Spatial and temporal adaptations within periodontal tissues and their interfaces result from functional loads. Functional loads can be physiologic and/or pathologic in nature. The prolonged effect of these loads can alter the overall biomechanics of a dentoalveolar fibrous joint (dentoalveolar joint) by changing the form of the tooth root and its socket. This "sculpting" of the tooth root and alveolar bony socket is a consequence of several mechano‐biological changes that occur within the periodontal complex of a load‐bearing dentoalveolar joint. These include changes in biochemical expressions, structure, elemental composition, and mechanical properties of alveolar bone, the underlying tissues of the roots of teeth, and their interfaces. These physicochemical changes in tissues continue to prompt mechano‐responsive biochemical activities at the attachment sites of periodontal ligament (soft) with bone (hard), and ligament with cementum (hard), which are the entheses of a load‐bearing dentoalveolar joint. Forces at soft‐hard tissue attachment sites between disparate materials with different stiffness values theoretically generate strain singularities or discontinuities. These discontinuities under prolonged functional loading increase the probability for failure to occur specifically at the enthesial zones. However, in a normal dentoalveolar joint, gradual stiffness gradients exist from ligament to bone, and from ligament to cementum. The gradual transitions in stiffness from softer ligament (lower stiffness) to harder bone or cementum (higher stiffness) or vice versa optimize tissue and interfacial strains. Optimization of tissue and ligament‐enthesial physical and chemical properties facilitates transmission of cyclic forces of varying magnitudes and frequencies that collectively maintain the overall biomechanics of a dentoalveolar joint. The objectives of this review are 3‐fold: (i) to illustrate physicochemical adaptations at the periodontal ligament entheses of a human periodontal complex affected by subgingival calculus; (ii) to demonstrate how to "program" the hallmarks of periodontitis in small‐scale vertebrates in vivo to generate spatiotemporal maps of physicochemical adaptations in a diseased dentoalveolar joint; and (iii) to correlate dentoalveolar joint biomechanics in healthy and diseased states to spatiotemporal maps of physicochemical adaptations within respective periodontal tissues. This interdisciplinary approach demonstrates that physicochemical adaptations within periodontal tissues using the mechanics of materials (tissue mechanics), materials science (tissue composition), and mechano‐biology (matrix molecules) can help explain the mechano‐adaptation of dentoalveolar joints in normal and diseased functional states. Multiscale biomechanics and mechano‐biology approaches can provide insights into the functional competence of a diseased relative to a normal dentoalveolar joint. Insights gathered from interdisciplinary and multiscale biomechanics approaches include the following: (i) physiologic loads related to chewing maintain a balance between mineral‐forming and‐resorbing biochemical cellular events, resulting in gradual stiffness gradients at the periodontal ligament entheses, and, in turn, sustain the overall biomechanics of a normal "healthy" dentoalveolar joint; (ii) pathologic loads resulting from tissue degradation and physical changes to the periodontal complex promote an abrupt stiffness gradient at the periodontal ligament entheses. The shift from gradual to an abrupt stiffness gradient could prompt a shift in the biochemical cascades, exacerbate mechano‐responsive biochemical expressions at periodontal ligament entheses farther away from the site of insult, and culminate in joint degradation; (iii) sustained pathologic function on periodontally diseased joints exacerbates degradation of periodontal ligament entheses providing insights into "rescue therapy", such as the use of an adequate "mechanocal dose" to regain joint function; and (iv) spatiotemporal maps of changes in biochemical expressions, and physicochemical properties of strain‐dominated affected sites, including the periodontal ligament entheses, can guide anatomy‐specific therapeutics for tissue regeneration and/or disease control with the purpose of regaining dentoalveolar joint function. Modulation of occlusal loads could minimize disease progression and potentially assist in regaining functional attachment of ligament to bone and/or ligament to cementum of the dentoalveolar joint. Elucidating mechanisms that drive the breakdown of the functionally active periodontal complex burdened with microbes will provide the required critical insights into regenerative medicine and/or biomimetic approaches that would facilitate rescue/regain of dentoalveolar joint function.